ASUHAN KEPERAWATAN GERONTIK PADA PASIEN ASAM URAT (GOUT ARTHRITIS) DENGAN INTERVERENSI PEMBERIAN JUS APEL TERHADAP PENURUNAN KADAR ASAM URAT DI PANTI WERDHA MARFATI TANGERANG GERIATRIC NURSING CARE FOR PATIENTS WITH GOUT ARTHRITIS WITH APPLE JUICE INTERV - Adawiyah, Sufia Al; Siti Robeatul Adawiyah; Regina Windyastuti (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
ABSTRACT/ABSTRAK Background: According to data from the World Health Organization, the prevalence of gout arthritis worldwide is quite high at 34.2%. Gout arthritis often occurs in developed countries such as the United States. Based on data, the prevalence of gout arthritis in the United States is 13.6% per 100,000 population. The prevalence of hyperuricemia in developing countries such as China and Taiwan continues to increase annually. Objective: This study aims to determine the effect of apple juice consumption on reducing uric acid levels. Method: Apple juice was administered as 100 ml of water with one apple daily for 6 days, once a day, administered directly, with uric acid levels measured pre- and post-intervention. Results: Apple juice consumption resulted in a decrease in uric acid levels over the 6-day period as assessed by pre- and post-intervention uric acid measurements. The initial uric acid level before apple juice consumption was 7.6 mg/dl, and after 6 days of apple juice consumption, it decreased to 5.1 mg/dl. Conclusion: The study demonstrates the influence of apple juice consumption on reducing pre- and post-intervention uric acid levels. The initial uric acid level was 7.6 mg/dl before apple juice consumption and decreased to 5.1 mg/dl after the intervention.Kata Kunci : Apple Juice, elderly, uric acid, lansia, jus apel, asam urat